2023
DOI: 10.3390/healthcare11040462
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Short Video Flow, Addiction, Serendipity, and Achievement Motivation among Chinese Vocational School Students: The Post-Epidemic Era Context

Abstract: Since the COVID-19 outbreak, people have been spending more time in the online world because of restrictions on face-to-face communication due to epidemic prevention controls. This has also brought the issue of Internet addiction, including the overuse and negative effects of short videos, to the forefront of attention. Past research has found that Internet addiction has a negative impact on well-being. However, there is a special concept of positive emotion called “serendipity” (小确幸). Serendipity provides a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Another study showed that both short video flow and short video addiction had significant negative relationships with achievement motivation in vocational school students (12). Moreover, it is known that short video addiction has positive significant relationships with learning avoidance motivation and negative significant relationships with learning commitment in vocational school students (45).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study showed that both short video flow and short video addiction had significant negative relationships with achievement motivation in vocational school students (12). Moreover, it is known that short video addiction has positive significant relationships with learning avoidance motivation and negative significant relationships with learning commitment in vocational school students (45).…”
Section: Discussionmentioning
confidence: 99%
“…The energetic, surprising, and entertaining content of short videos can cause individuals to experience the flow very much. Short video flow is described as the state of high enjoyment and immersion one gets while watching a video (12). It has been suggested that flow experiences are also associated with various behavioral addictions (13,14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problematic usage is generally considered to be detrimental to users. Students in particular love short videos, but because of the immersive nature of the videos, many students can experience associated problems, and some even become addicted [ 2 , 3 , 4 ]. Therefore, Hong et al pointed out that video addiction behaviors have had a very large negative impact on the study and life of students of different school ages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%